Simplifying
17x + -12 = 114 + 3x
Reorder the terms:
-12 + 17x = 114 + 3x
Solving
-12 + 17x = 114 + 3x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-3x' to each side of the equation.
-12 + 17x + -3x = 114 + 3x + -3x
Combine like terms: 17x + -3x = 14x
-12 + 14x = 114 + 3x + -3x
Combine like terms: 3x + -3x = 0
-12 + 14x = 114 + 0
-12 + 14x = 114
Add '12' to each side of the equation.
-12 + 12 + 14x = 114 + 12
Combine like terms: -12 + 12 = 0
0 + 14x = 114 + 12
14x = 114 + 12
Combine like terms: 114 + 12 = 126
14x = 126
Divide each side by '14'.
x = 9
Simplifying
x = 9